The Minimal Clinically Important Difference of the Anterior Skull Base Nasal Inventory-12. Issue 2 (4th August 2017) - Gravbrot, Nicholas; Kelly, Daniel F; Milligan, John; Griffiths, Chester F; Barkhoudarian, Garni; Jahnke, Heidi; White, William L; Little, Andrew S
Abstract: BACKGROUND: The minimal clinically important difference (MCID) is defined as the smallest change in health-related quality of life (QOL) that patients consider meaningful. The MCID is essential for determining clinically significant changes, rather than simply statistically significant changes, in QOL scores. The Anterior Skull Base Nasal Inventory-12 (ASK Nasal-12), a site-specific sinonasal QOL instrument, has emerged as a standard instrument for assessing QOL in patients who have undergone endonasal transsphenoidal surgery. OBJECTIVE: To determine the MCID for the ASK Nasal-12. METHODS: Distribution- and anchor-based methods were used to determine the MCID for the ASK Nasal-12 based on raw data from a multicenter prospective QOL study of 218 patients. RESULTS: Two distribution-based statistical methods, the one-half standard deviation method and the effect-size method, both yielded MCIDs of 0.37 (medium effect). The first anchor-based method, using the 2-wk postoperative overall nasal functioning item as the anchor, yielded an MCID of 0.31. The second anchor-based method, using the 2-wk postoperative Short Form Health Survey 8 bodily pain item as the anchor, yielded an MCID of 0.29. CONCLUSION: The largest MCID obtained for the ASK Nasal-12 using 4 statistical methods 2 wk postoperatively was 0.37. This information provides clinicians with an essential context for determining the clinical significance of changes in QOL scores after interventions. Our results will help clinicians better interpret QOL scores and design future studies that are powered to detect meaningful QOL changes.